2009
DOI: 10.1080/09585190902770547
|View full text |Cite
|
Sign up to set email alerts
|

Fits in strategic human resource management and methodological challenge: empirical evidence of influence of empowerment and compensation practices on human resource performance in Canadian firms

Abstract: To cite this article: Denis Chênevert & Michel Tremblay (2009) Fits in strategic human resource management and methodological challenge: empirical evidence of influence of empowerment and compensation practices on human resource performance in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 96 publications
1
32
0
Order By: Relevance
“…Researchers suggest that empowering employees results in extra responsibility which needs to be rewarded; otherwise, employees tend to interpret empowerment as an extra duty which increases their workload (Erstad, 1997;Rafiq and Ahmed, 1998). Recently, Chenevert and Tremblay (2009) found that the use of an extensive empowerment strategy reduces voluntary turnover when accompanied by a compensation program that rewards performance. Based on the previous research, we hypothesize the following:…”
Section: Service Rewardsmentioning
confidence: 97%
“…Researchers suggest that empowering employees results in extra responsibility which needs to be rewarded; otherwise, employees tend to interpret empowerment as an extra duty which increases their workload (Erstad, 1997;Rafiq and Ahmed, 1998). Recently, Chenevert and Tremblay (2009) found that the use of an extensive empowerment strategy reduces voluntary turnover when accompanied by a compensation program that rewards performance. Based on the previous research, we hypothesize the following:…”
Section: Service Rewardsmentioning
confidence: 97%
“…Contingency and configurational theories -where researchers assert that superior performance is attributable to proper congruence or fit between structural design and contextual variables -dominate the alignment research (Venkatraman, 1989;Iivari, 1992;Umanath, 2003;Chênevert and Tremblay, 2009). This perspective assumes that misalignment or misfit degrades performance (Iivari, 1992;Bergeron et al, 2001;Meilich, 2006).…”
Section: Measures Of the Alignment Constructmentioning
confidence: 99%
“…Therefore, the researchers emphasize the need for cohesive and coherent theories which are aligned to both planning and organizational strategy to properly sustain HRM. This indicates that policies and practices of HRM are likely to vary among organizations, but they need to be aligned with business strategy (Chênevert & Tremblay, 2009). According to Boxall and Purcell (2000), the impact of the person's HRM practices relies upon both the nature of the impact of other HRM practices as well as the business strategy.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%